Status Kesehatan Psikososial dengan Risiko Depresi pada Wanita Hamil pada Masa Pandemi Covid-19 di Kebumen - Rahmadhani, Wulan; Mutoharoh, Siti; Kusumastuti, Kusumastuti (Universitas Aisyah Pringsewu, 2022)
Pregnancy involved physiological and social changes, which mothers are expected to adapt to biopsychosocial changes. Failure to make such an adoption would be accompanied by an increased risk of prenatal depression in pregnant mothers. This research was to determine the relationship between psychosocial health and the risk of depression in pregnant mothers. This descriptive-analytic study was carried out on 540 pregnant (39 respondents in the first, 320 in the second, and 181 respondents third trimesters, respectively). The pregnant mother who attended the outpatient clinic and met the inclusion criteria were selected using haphazard sampling, as a non-probability sampling method. The data were collected through a researcher-made questionnaire, the Pregnancy Psychosocial Health Assessment Scale (PPHAS), and the Edinburgh Postnatal Depression Scale (EPDS). Data analysis was performed in SPSS using descriptive statistics, Mann-Whitney U test, and Kruskal Wallis test. The pregnant mother had a depression risk of 27.8% and a mean depression score of 9.99±2.81. The total mean score of PPHAS was obtained as 4.05±0.45. The risk of depression showed a statistically negative relationship with the total and sub-dimension mean scores of PPHAS, as well as the mean EPDS score (p less than 0.001). A pregnant mother with lower psychosocial health status was more likely to have a risk of depression. On another hand, the risk of depression in pregnant women was influenced by many factors that determine by their psychosocial health.Abstrak: Kehamilan melibatkan perubahan fisiologis, psikologis, dan sosial dimana wanita hamil diharapkan untuk beradaptasi dengan perubahan biopsikososial. Kegagalan untuk beradaptasi dengan perubahan tersebut akan disertai dengan peningkatan risiko depresi prenatal pada wanita hamil. Penelitian ini bertujuan untuk mengetahui hubungan status kesehatan psikososial dengan risiko depresi pada wanita hamil. Penelitian deskriptif-analitik ini melibatkan 540 wanita hamil (masing-masing 39, 320, dan 181 kasus pada trimester pertama, kedua, dan ketiga) di Kebumen. Wanita hamil yang berobat jalan di poliklinik dan memenuhi kriteria inklusi dipilih dengan menggunakan metode non-probability random sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner yang disusun berdasarkan Pregnancy Psychosocial Health Assessment Scale (PPHAS) dan Edinburgh Postnatal Depression Scale (EPDS). Kemudian, data dianalisis dengan software SPSS menggunakan statistik deskriptif yaitu uji Mann-Whitney U dan uji Kruskal Wallis. Wanita hamil memiliki risiko depresi mencapai 28,2% dan rerata skor depresi sebesar 9,41±4,8. Total skor rata-rata PPHAS mencapai 4,05 ± 0,45. Risiko depresi menunjukkan hubungan negatif secara statistik dengan skor rata-rata total dan subdimensi PPHAS, serta skor rata-rata EPDS (p kurang dari 0,001). Wanita hamil dengan status kesehatan psikososial rendah lebih berisiko mengalami depresi. Dengan kata lain, risiko depresi pada wanita hamil dipengaruhi oleh faktor-faktor yang menentukan kesehatan psikososial mereka.